Real-world data in late presentation of HIV infection in Suzhou, China: Results from four consecutive cross-sectional surveys, 2017–2020 - Xu, Zhihui; Shen, Qiang; Wang, Di; Dong, Zefeng; Han, Weining; Tian, Runfang; Zhou, Kai; Ya, Xuerong; Hu, Haiyang (Frontiers in Public Health, 2023)
Objectives: This study aimed to examine the real prevalence of late presentation of HIV infection and to identify factors associated with late HIV presentation among patients with newly diagnosed HIV/AIDS in Suzhou, China. Methods: Patients with newly diagnosed HIV/AIDS who registered in national AIDS surveillance system from 2017 to 2020 were included in this study. Late presentation (LP) of HIV infection was defined as HIV diagnosis with a CD4 count < 350 cells/μL or an AIDS-defining event. Multivariable logistic regression analyses were used to identify factors associated with LP. Results: A total of 2300 patients were enrolled. 1325 were classified as late presenters, showing a high percentage of 57.6% (95% CI: 54.5%-60.7%) and a rise (P=0.004) over the four-year period. Patients with newly diagnosed HIV/AIDS who were older than 24 years of age (aOR = 1.549, P = 0.001 for 25-39 years; aOR = 2.389, P < 0.001 for 40 years and older), were Suzhou registered residents (aOR = 1.259, P = 0.026), and were from inpatient and outpatient (aOR = 1.935, P < 0.001) were more likely to be late presentation. Conclusions: This study showed a high percentage and a rise of late presentation of HIV infection among patients with newly diagnosed HIV/AIDS in Suzhou, China, which is a challenge for future prevention and control of AIDS. Targeted measures should be urgently implemented to reduce late HIV diagnosis.